Source Injection Induced Off-State Breakdown and Its Improvement by Enhanced Back Barrier with Fluorine Ion Implantation in AlGaN/GaN HEMTs - Wang, Maojun; Chen, Kevin J. (IEEE INTERNATIONAL ELECTRON DEVICES MEETING 2008, TECHNICAL DIGEST, 2008)
The mechanisms of AlGaN/GaN HEMT's off-state breakdown are investigated. Both the source- and gate-injection induced impact ionizations are identified with the former leading to premature three-terminal breakdown. A 35% improvement of the breakdown voltage could be achieved in an enhanced back barrier HEMT by implanting fluorine ions under the channel region and effectively block the source injection through the buffer layer.